Daily field checking list by Walter Rosene, April 16, 1939 - Rosene, Walter M., Sr., 1880-1941et al; Iowa Ornithologists' Unionet al
Daily field checking list of birds observed in Boone County by Walter Rosene and Robert Walker, April 16, 1939. Also notes the three young Great Horned Owls now fill the nest cavity. Plustek--flatbed